Screening COVID-19 Suspected Cases and Determining the Associated Factors - Tesfaw, Lijalem Melie; Kassie, Aragaw Bizualem (Frontiers in Public Health, 2022)
Background: Confirmed cases of corona-virus in Africa, particularly in Ethiopia are increasing rapidly following improved testing. Though most peoples show the main symptoms of COVID-19, they are not volunteering to visit the hospital and confirm whether the virus is in their body. This study is aimed at assessing suspected COVID-19 participants and associated factors among the metropolitan city population of the Amhara region, Ethiopia. Methods: A cross-sectional study design involving participants recruited from Amhara Metropolitan cities was implemented. A total of 1288 randomly selected participants completed an actively screening test questionnaire that was used to assess whether the participants were suspected of coronavirus. The statistical analysis chi-square statistic and binary logistic regression were implemented. Results: From 1288 study participants, 788 (61.2%) and 500 (38.8) were male and female, respectively. 77.5% of the participant were from orthodox religion and 12.2% live in the rural area permanently. As compared to female participants (45.9%) the number of suspected male participants (54.1%) was higher. As compared to communities in Woldya metropolitan city, communities in Bahir Dar (aOR=0.101;95%CI=0.065,0.156), Gondar ( aOR=0.072;95%CI = 0.043,0.122), and Debre Markos (aOR=0.368;95%CI=0.271,0.501) metropolitan city were less likely to be suspected of coronavirus. Compared to the employed participants, unemployed participants had lower odds of being suspected of coronavirus (aOR=0.147; 95% CI=0.1160.186). Conclusion: The prevalence of suspected cases of coronavirus in Amhara metropolitan city was considerably high. City of residence, marital status, work status, hospital use, permanent residence, and source of information were important determinants of a suspected case of coronavirus. Thus, timely diagnosis of suspected cases of coronavirus and taking the appropriate remedial action help to reduce the spread and mortality rate. Keywords: Coronavirus, Binary logistic regression, suspected case, Ethiopia.